Harnessing Open Educational Resources to the Challenges of Teacher Education in Sub-Saharan Africa - Thakrar, Jayshree; Wolfenden, Freda; Zinn, Denise (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The challenges to teacher educators in sub-Saharan Africa are acute. This paper describes how the Teacher Education in Sub-Saharan Africa (TESSA) consortium is working within institutional and national policy systems to support school-based teacher professional development. The TESSA consortium (13 African institutions and 5 international organisations delivering teacher education across 9 countries) designed and produced a bank of open educational resources (OERs) to guide teachers’ classroom practices in school-based teacher education. Drawing on examples from the TESSA consortium and from the University of Fort Hare, South Africa, the authors categorize the forms of TESSA OER integration as highly structured, loosely structured, or guided use. The paper concludes by outlining success factors for the integration of OERs: accessibility, adequate resources, support for teachers, accommodation of local cultural and institutional practices, and sustainable funding.